Consequences of Drug Abuse among Female and Male Population of Karachi: A Statistical Surveyed Approach - Sultan, Rana Saba; Masudi, Jawed Aziz; Siddiqui, Afaq Ahmed; Mansoor, Najia (International Journal of Criminology and Sociology, 2015)
Drugs are chemicals. Different drugs, because of their chemical structures, can affect the body in different ways. The most obvious effects of drug abuse which are manifested in the individuals include ill health, sickness and ultimately, death. The social life is also not spared by the hazardous impacts of the problem. Whereas the load at health department is increased, rise in crime rate is also a perilous effect faced by the society related to the growth of abusers in the country. The following study highlights the different effects that can influence male and female drug abusers to get rid of their drug misuse habits. Abusers age, level of awareness about drugs adverse effects, their encounters to health ailments including the life threatening infection HIV, and involvement in crimes were included in the survey which was carried out in Karachi in order to assess the magnitude of this problem.